UPAYA MENINGKATKAN PRESTASI BELAJAR PRAKARYA DAN KEWIRAUSAHAAN DENGAN METODE STRUKTURAL SUMBANG SARAN PADA MATERI MEDIA PROMOSI DI KELAS XII TP-B SMK NEGERI 1 CIMAHI TAHUN 2017/2018 - Kushandayani, Kushandayani (IKIP Siliwangi Bandung, 2020)
The main task of the teacher is to be responsible for helping students in learning. In the teaching and learning process, it is the teacher who delivers lessons, solves problems that occur in class, makes student learning evaluations, both before, during and after the lesson (Combs, 1984: 11-13). To play a role and carry out these tasks, a teacher is expected to have high professional abilities. In this connection, to get to know their students well, teachers need to have the ability to make a diagnosis and be familiar with the most effective ways to help students grow according to their respective potential. This research uses action research as many as three rounds. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The targets of this study were students of class XII TP-B. The data obtained were formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (62.50%), cycle II (75.00%), cycle III (93.75%). The conclusion from this research is that the combination of lecture methods with brainstorming methods can have a positive effect on the achievement and motivation of students of Class XII TP-B SMK Negeri 1 Cimahi and this learning model can be used as an alternative to learning Craft and Entrepreneurship.